On Integral Operator Defined by Convolution Involving Hybergeometric Functions - K. Al-Shaqsi; M. Darus (International Journal of Mathematics and Mathematical Sciences)
For λ>−1 and μ≥0, we consider a liner operator Iλμ on the class 𝒜 of analytic functions in the unit disk defined by the convolution (fμ)(−1)∗f(z), where fμ=(1−μ)z2F1(a,b,c;z)+μz(z2F1(a,b,c;z))', and introduce a certain new subclass of 𝒜 using this operator. Several interesting properties of these classes are obtained.